2011
DOI: 10.1016/j.cmet.2011.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Control of Pancreatic β Cell Regeneration by Glucose Metabolism

Abstract: Recent studies revealed a surprising regenerative capacity of insulin-producing β cells in mice, suggesting that regenerative therapy for human diabetes could in principle be achieved. Physiologic β cell regeneration under stressed conditions relies on accelerated proliferation of surviving β cells, but the factors that trigger and control this response remain unclear. Using islet transplantation experiments, we show that β cell mass is controlled systemically rather than by local factors such as tissue damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
274
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(306 citation statements)
references
References 55 publications
24
274
1
3
Order By: Relevance
“…In wild-type mice fed a high-fat diet, beta cell mass increases to meet the increased demand for insulin, and this compensatory hyperplasia is diminished in mice that are haplo-insufficient for glucokinase (Gck +/− mice) [24]. Similarly, it has been shown that glucokinase plays a critical role in restoring beta cell mass following acute beta cell loss triggered by transgenic manipulation [27]. Clinically, it has been observed that a gain-of-function glucokinase mutation results in enlarged islets [7,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In wild-type mice fed a high-fat diet, beta cell mass increases to meet the increased demand for insulin, and this compensatory hyperplasia is diminished in mice that are haplo-insufficient for glucokinase (Gck +/− mice) [24]. Similarly, it has been shown that glucokinase plays a critical role in restoring beta cell mass following acute beta cell loss triggered by transgenic manipulation [27]. Clinically, it has been observed that a gain-of-function glucokinase mutation results in enlarged islets [7,10].…”
Section: Discussionmentioning
confidence: 99%
“…Various lines of indirect evidence suggest that pharmacological interventions that augment glucokinase activity may favour mechanisms that slow or prevent beta cell loss [22,23] or promote beta cell proliferation in vivo [3,[24][25][26][27]. The present experiments were undertaken to address an ongoing need for data to test and shed further light on this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…In short, there are reasons to believe the answer is no, miRNAs still act to strictly regulate secretion even during chronic hyperglycemia. Another important aspect of β-cell function is its concomitant ability to proliferate to increase cellular number and mass in response to increased demand for insulin and glucose has long been known as a potent regulator of β-cell proliferation [32] [33] [34]. The mouse knockouts for miR-375 and Ago2 in the β-cell both showed loss of compensatory proliferation after crossing these models onto the ob/ob background indicating miRNA function is essential for this adaptive response.…”
Section: Identification Of Microrna Targets In the β-Cellmentioning
confidence: 99%
“…For example, in rats, glucose infusion increases beta cell numbers by 50% [81], with neogenesis of precursor cells being a dominant contributor to the increased mass [82]. Furthermore, glucose promotes beta cell survival by suppressing a constitutive apoptotic programme in vivo [83], and there is evidence that chronic changes in beta cell glucose metabolism induced by genetic or pharmacological manipulation of glucokinase can regulate beta cell mass regeneration in vivo [84]. Paradoxically, chronic hyperglycaemia promotes glucotoxicity which, in turn, exacerbates diabetes by increasing apoptosis [85].…”
Section: Contributors To Maintenance Of Islet Cell Mass In Adult Rodentsmentioning
confidence: 99%